2009
DOI: 10.1002/adem.200900103
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Variation and Strain Distribution in Magnesium Alloy AZ31 Processed by Multi‐pass Caliber Rolling

Abstract: The evolution of microstructure and hardness with equivalent strain was studied in magnesium alloy AZ31 bars fabricated using a process of multi‐pass caliber rolling at 473 K. The inhomogeneity of hardness throughout the cross section in the rolled bars was very similar to that of the strain predicted from FE simulation. The caliber rolling produced a fine‐grain structure below 2.5 µm in a bulk sample with a length of over 1000 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…The billet was passed through 6 or 14 times and twice for the final groove to control the cross-sectional shape of the bar, and then was quenched in water (hereafter, denoted as 7-and 15-passed alloys). The detailed experimental procedure is reported elsewhere [25,26] .…”
Section: Methodsmentioning
confidence: 99%
“…The billet was passed through 6 or 14 times and twice for the final groove to control the cross-sectional shape of the bar, and then was quenched in water (hereafter, denoted as 7-and 15-passed alloys). The detailed experimental procedure is reported elsewhere [25,26] .…”
Section: Methodsmentioning
confidence: 99%
“…Inoue et al investigated the strain distribution in the SM490 steel by a finite element analysis and deformed microstructure observation. 7,8) Higher strain accumulation at the corner area of the specimen was found to be higher than the center area.…”
Section: Introductionmentioning
confidence: 94%
“…Inoue et al 8) evaluated by a finite element analysis that the equivalent strain ¾ eq introduced by 94%…”
Section: % Rolled 95% Rolled As Castmentioning
confidence: 99%
“…Next, the bar was tempered at 773 K for 1 h and then water-cooled. The SM490 sample with a chemical composition of 0.15 C, 0.3 Si and 1.5 Mn was heated to 900°C and held for 1 h, followed by air cooling (Inoue et al (2009)). The principal axes of the rolled bar in this study are defined as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%